2016
DOI: 10.2147/mder.s121712
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of strap tension during non-invasive ventilation mask application: a combined biomechanical and biomarker approach

Abstract: Non-invasive ventilation is commonly used for respiratory support. However, in some cases, mask application can cause pressure ulcers to specific features of the face, resulting in pain and reduced quality of life for the individual. This study investigated the effects of mask strap tension on the biomechanical and biomarker responses at the skin interface. Healthy participants (n = 13) were recruited and assigned two different masks in a random order, which were fitted with three strap conditions representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 31 publications
8
67
2
Order By: Relevance
“…Specifically, the greatest reduction of local contact forces offered by the use of the dressing cuts was at the bridge of the nose. These findings are consistent with previously published research demonstrating that the nose is the most common location for NIV mask‐related PU development . Anatomically, the bridge of the nose is characterised by curved geometry with minimal soft tissue coverage, hence with structural tendency to greater tissue deformations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, the greatest reduction of local contact forces offered by the use of the dressing cuts was at the bridge of the nose. These findings are consistent with previously published research demonstrating that the nose is the most common location for NIV mask‐related PU development . Anatomically, the bridge of the nose is characterised by curved geometry with minimal soft tissue coverage, hence with structural tendency to greater tissue deformations.…”
Section: Discussionsupporting
confidence: 92%
“…The contact forces developed at the cheeks were considerably lower than those developed at the bridge of the nose or at the chin, being consistent with previously published literature . Moreover, we found that the effect of the dressing cuts on the cheeks was indistinguishable across the experimental study group, possibly because, as stated above, the cheeks contain thicker soft tissue masses and are relatively distant from bony prominences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations